KORELASI PENGUASAAN DIKSI TERHADAP KETERAMPILAN MENULIS TEKS CERPEN - Tazkia Mayada; Anshari Anshari; Sakaria Sakaria (Fakultas Teknik Universitas Negeri Makassar, 2026)
This study aims to analyze the correlation between vocabulary mastery and short story writing skills among seventh-grade students at SMP Negeri 24 Makassar. The research conducted is descriptive correlational in nature and employs a quantitative approach. The population of this study was all seventh-grade students at SMP Negeri 24 Makassar, with a sample determined using purposive sampling, namely 34 seventh-grade students. Data collection techniques used two instruments, namely a multiple-choice vocabulary mastery test and a short story writing skills test. Data analysis techniques consisted of descriptive statistics to describe the data for each variable and inferential statistics with Spearman's rank correlation test. The results showed that the students' vocabulary mastery level was in the sufficient category with an average score of 62.35. Meanwhile, the students' short story writing skills were in the low category with an average score of 35.29. The Spearman correlation test obtained a correlation coefficient of 0.293 with a significance of 0.093 (p > 0.05), which means that there was no significant correlation between vocabulary mastery and short story writing skills. These findings indicate that short story writing skills are not determined by vocabulary mastery but are influenced by factors such as text structure mastery, creativity, reading experience, and writing motivation.